Neuromuscular and hormonal adaptations to resistance training: special effects of time of day of training - Sedliak, M. (Studies in Sport, Physical Education and Health, 2009)
The majority of the processes in human physiology and behaviour exhibit daily Variation. Neuromuscular performance has been repeatedly shown to be lower in the morning hours compared to the rest of the day. However, the scientific data available provide somewhat conflicting results on the origin and mechanisms of diurnal Variation in maximum strength and power. In addition, very limited scientific evidence exists as to whether this diurnal Variation can be diminished by time-of-day-specific resistance training. The present study was designed to obtain more information on the mechanisms behind both diurnal Variation in muscle strength and power, and the mechanisms behind adaptations to time-of-day-specific resistance training. The present results on the mechanism of diurnal Variation suggest that neither myoclectrical activity nor muscle tone could fully explain the diurnal Variation in maximum strength. It seems plausible that processes within die muscle tissue are at least partiy responsible for the diurnal Variation. Importantly, it was noted that diurnal patterns were affected by test order-related confounding factors. Anticipatory stress prior to the first Session, and learning and/or improved muscular coordination due to the frequent testing, seemed to be the major confounding effect regardless of the test design. Anticipatory stress could induce a masking effect during the first morning test Session, resulting in transient elevation of both serum cortisol concentrations and temperaturc Ievels. The findings on the training-induced adaptations indicate that resistance training performed in the morning, but not in the afternoon, attenuated the diurnal Variation in maximum strength and power. However, the absolute increase in maximum voluntary strength and muscle size was similar regardless of the time of day of training. Myoelectrical activity increased in both training groups but with no obvious effect of time of day. Interestingly, time-of-day-specific training adaptations most likely occurred also at the psychological level, by reducing the anticipatory stress, but only in the group of subjects who repeatedly trained in the morning hours. It can be suggested that time-of-day-specific strength training may be bcneficial in sports where maximum strength performance needs to peak at a particular time of day, especially in the morning hours.